PENGARUH IKLIM ORGANISASIONAL, AFEK POSITIF SPIRAL DALAM KELOMPOK KERJA, DAN SPIRITUALITAS KERJA TERHADAP KOMITMEN KERJA KARYAWAN REKTORAT UNIVERSITAS BRAWIJAYA - Ika Adita Silviandari; Ika Rahma Susilawati; Ika Widyarini; Ilhamuddin Ilhamuddin (MANASA, 2013)
This research studied the effect of organizational climate, spiral positive affect in workgroup, and spirituality at work toward occupational commitment using field survey research method. 90 subjects were involved and sampled by using cluster sampling method. The variables were assessed with organizational climate, spiral positive affect in workgroup, spirituality at work, and occupational commitment Likert-like scales. Multiple linier regression analyses indicated that organizational climate (X1), spiral positive affect in workgroup (X2), and spirituality at work (X3) have 38,6 % simultaneous contributions on occupational commitment (R2=0.386; F: 18.031). But only spiral positive affect in workgroup can solely predict occupational commitment signifcantly (t = 2.016; p=0.047< 0.05). These findings suggest that despite the influence of organizational climate and individual spirituality at work, experiencing pleasure of working in group/ team foster greater employee commitment.